Self-Regulation Strategies Self-Report Inventory (SRSI-SR): evidences of validity, reliability and equity in university students from the city of Piura - Moscol Seminario, Jimena (2021)
The general objective of this research was to analyse the evidence of validity, reliability and equity of the Self Regulation Strategy Inventory—Self- Report. 189 college students participated between the ages of 18 and 42. The results obtained were found that items 4, 8 and 9 did not have adequate rates of corrected homogeneity or communality. Evidence of convergent validity in relation to selfconcept and academic self-efficacy and discriminatory validity in relation to exam anxiety. In addition, exploratory factorial analysis reported four factors with an explained variance of 69.55%, while the final confirmatory analysis, demonstrated fit of the four-factor correlated model (X2= 93,654, df= 71, X2/df= 1.31, CFI= .974, TLI= .967, RMSEA= .071, SRMR= .044). In addition, reliability was determined through the Alpha Ordinal coefficient by reporting an index in its dimensions of .85 in OT, .79 in HIR, .86 in OE, .86 in BI, and the total reliability of .96. Finally, evidence of equity by sex and age was found, affirming that the score comparison of this instrument based on these variables will be valid and reliable in subsequent studies.